Efeito do disseleneto de difenila sobre a toxicidade induzida por cloreto de mercúrio em camundongos - Brandão, Ricardo (2008)
Mercury is a metal without physiological functions in human body and is toxic to human beings. This metal has many applications in industry and, therefore it is very important in occupational and environmental exposure. The toxicity of mercury depends on the form of the metal and can affect several organs, such as brain, kidney and liver. In addition, mercury can cause alteration in hematological and immunological systems. The oxidative stress seems to be involved in toxicity induced by mercury, since this metal may cause an increase in the production of reactive oxygen species (ROS) and disturbances in enzymatic and non-enzymatic antioxidant defense systems. Thus, in addition to conventional therapies using chelating agents, therapies using antioxidants are tested in an attempt to reduce the toxic effects of this metal. Since diphenyl diselenide (PhSe)2 has several pharmacological properties, including antioxidant action, our goal was to verify the effect of this compound in different models of exposure to mercuric chloride (HgCl2) in mice. The use of another antioxidant agent, Nacetylcysteine (NAC), and a chelating agent of reference, 2,3-dimercapto-1-propanosulfonato (DMPS), were also evaluated. The results showed that the concomitant and acute exposure to HgCl2 and therapeutic agents tested presented toxic effects. In fact, the administration of DMPS and NAC, in animals exposed to HgCl2, caused renal toxicity in mice, which was evidenced by an increase in the urea and creatinine levels and by reduction on renal Na+, K+-ATPase activity. This can be explained by a possible formation of complexes between the metal and these agents. The administration of (PhSe)2 caused 100% of death in animals exposed to HgCl2. The toxic effects of HgCl2 + (PhSe)2 association affects the hepatic tissue and especially the renal tissue. Hepatic damage was characterized by an increase in the lipid peroxidation levels and reduction in catalase activity from animals of HgCl2 + (PhSe)2 group. Renal damage was characterized by biochemical markers in plasma and urine of mice. Moreover, mice exposed to the association between HgCl2 and (PhSe)2 showed inhibitions in renal glutathione S-transferase (GST) and Na+, K+-ATPase activities. The oxidative damage in renal tissue was evidenced by increase in the lipid peroxidation levels and increase in ascorbic acid concentration in mice exposed to HgCl2 + (PhSe)2 group. Increased levels of hemoglobin and hematocrit were also observed in mice of HgCl2 + (PhSe)2 group and renal damage seems to be involved in this effect. The formation of a complex between HgCl2 and (PhSe)2, which displays pro-oxidant activity, is the most probably hypothesis to explain this toxicity. We observed also that the preventive therapy with (PhSe)2 was effective in protecting against immunological and hematological alterations induced by subchronic HgCl2 exposure. In fact, exposure to HgCl2 caused anemia in mice, which was observed by reducing in the hemoglobin, erythrocytes and hematocrit levels. Moreover, levels of leukocytes and platelets were also reduced by exposure to HgCl2. The immunological changes were evidenced by increase in immunoglobulins levels. All these changes, hematological and immunological, were reduced by (PhSe)2 pre-treatment. The antioxidant activity of this selenium compound seems to be involved in this mechanism of protection, as well as the formation of a inactive ternary complex between mercury, selenium and selenoprotein P. (PhSe)2 also presented similar effects when compared to DMPS in restored renal and hematological damage observed after subchronic exposure to HgCl2. The hematological changes (decrease in erythrocytes, leukocytes and platelets levels) and changes in renal tissue, observed by increase in the plasmatic urea, creatinine, and uric acid levels and renal lipid peroxidation, induced by exposure to HgCl2, were reversed by (PhSe)2 and DMPS, individually administered. However, the combined use of (PhSe)2 and DMPS did not present good results, since the individual therapies with these two agents were more effective than the combined administration. Based on these results, we can conclude that the use of (PhSe)2 against the HgCl2 toxicity should be further studied, since, depending on the experimental model, the results can be beneficial or there may be a potentiation of the toxic effects of mercury.